Failure of B-Lynch Compression Suture in a Patient with Couvelaire Uterus and Uterine Atony - Pınar Çilesiz Göksedef; Mushviqe Hasanova (Haseki Tıp Bülteni)
In this paper, we aimed to discuss the reliability of B-Lynch suture, especially in patients with Couveliare uterus, and to present a patient who underwent bilateral uterine artery ligation in addition to B-Lynch compression suture for uterine atony resulting from abruptio placentae and developed retroperitoneal hematoma due to uterine laceration in the postpartum period.